Filling-in rivalry : perceptual alternations in the absence of retinal image conflict - Chen, Zhimin (2020)
During perceptual rivalry, an observer's perceptual experience alternates over time despite constant sensory stimulation. Perceptual alternations are thought to be driven by conflicting or ambiguous retinal image features at a particular spatial location and modulated by global context from surrounding locations. However, rivalry can also occur between two illusory stimuli-such as two filled-in stimuli within the retinal blind spot. In this "filling-in rivalry," what observers perceive in the blind spot changes in the absence of local stimulation. It remains unclear if filling-in rivalry shares common mechanisms with other types of rivalry. We measured the dynamics of rivalry between filled-in percepts in the blind spot, finding a high degree of exclusivity (perceptual dominance of one filled-in percept, rather than a perception of transparency), alternation rates that were highly consistent for individual observers, and dynamics that closely resembled other forms of perceptual rivalry. The results suggest that mechanisms common to a wide range of rivalry situations need not rely on conflicting retinal image signals.